Cefotetan-Induced Hemolytic Anemia: Case Series and Review. (December 2019) - Lim, Kathlyn; Tran, Hai; Hirai-Yang, Angela; Vakil, Niyati; Marks, Gregory; Klapper, Ellen
Purpose: To raise awareness of cefotetan-induced hemolytic anemia, a known rare but serious side effect that occurred in 5 patients at our medical center. Summary: Five cases of cefotetan-induced hemolytic anemia, which presented over the period of a single year at our center, are described. In each case, hemolytic anemia was confirmed by testing for the presence of anti-cefotetan antibodies. Each case occurred approximately 1 to 2 weeks following exposure to the drug. All five patients survived. A brief review of drug-induced immune hemolytic anemia (DIIHA) is also discussed. Conclusion: DIIHA may be difficult to distinguish from other causes of hemolytic anemia, but should be included in the differential in patients exposed to medications associated with DIIHA. Once suspected, antibody testing should be performed, and once diagnosed, further exposure should be avoided.